Influence of tibial plateau leveling osteotomy and tibial tuberosity advancement on passive laxity of the cranial cruciate deficient stifle in dogs. Issue 3 (17th February 2019) - Ober, Ciprian A.; Factor, Gilad; Meiner, Yaron; Segev, Gilad; Shipov, Anna; Milgram, Joshua
Abstract: Objective: To evaluate the effect of tibial plateau leveling osteotomy (TPLO) and tibial tuberosity transposition (TTA) on craniocaudal stability of the cranial cruciate ligament (CCL) deficient stifle at 3 joint angles. Study design: Ex vivo biomechanical study. Sample population: Eight stifles from 4 dogs. Methods: One of the hind limbs was randomly assigned to undergo TPLO or TTA, with the contralateral limb assigned to the alternate procedure. Each specimen was tested with the stifle at 150°, 135°, and 120° of flexion. Cranial translation of the tibia relative to the femur was measured under cranial loads ranging from 0.2 to 2.0 kg with a single motion tracking sensor (Nest of Birds) fixed to the tibia. Each stifle was tested before and after transection of the CCL and after performing the assigned procedure. Results: Tibial plateau leveling osteotomy and TTA caused a decrease in the cranial translation of the tibia relative to the femur, especially at greater angles of flexion. Tibial plateau leveling osteotomy caused a greater decrease in tibial cranial translation and was associated with a degree of translation that did not differ from joints with intact CCL, regardless of the degree of stifle flexion. Conclusion: Tibial plateau leveling osteotomy and TTA caused an angle dependent decrease in craniocaudal translation of the tibia in the CCL deficient stifle. Only TPLO restored translations similar to those of the intact joint at all angles tested. Clinical impact: Tibial plateau leveling osteotomy and TTA provide passive stability to the stifle. Tibial plateau leveling osteotomy seems more effective than TTA at restoring craniocaudal stability of the stifle.